2015
DOI: 10.1248/yakushi.15-00021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Thickener on Disintegration and Dissolution of Magnesium Oxide Tablets

Abstract: 835YAKUGAKU ZASSHI 135(6) 835-840 (2015) It has been reported that magnesium oxide tablets are excreted in a non-disintegrated state in the stool of patients when the tablets are administered after being immersed in a food thickener. Therefore we examined whether immersion in a food thickener aŠects the pharmacological eŠect in patients taking magnesium oxide tablets, and whether immersion aŠects its disintegration and solubility. The mean dosage (1705 mg/d) was higher for patients who took tablets after imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…1,2) However, there have been reports of undissolved tablets observed in the stool of patients taking magnesium oxide tablets, which have been immersed in a thickening agent; these thickening agents may aŠect the disintegration or dissolution of magnesium oxide. 3) In addition, the thickening agents may also aŠect the disintegration of quick-dissolving tablets such as oral-disintegrating tablets. 4,5) In this report, we examine the eŠect of immersion of a thickening agent on the inhibitory eŠect of frequently administered voglibose oral-disintegrating tablets on the incremental elevation of blood sugar levels, with the aim of improving post-prandial hyperglycemia in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) However, there have been reports of undissolved tablets observed in the stool of patients taking magnesium oxide tablets, which have been immersed in a thickening agent; these thickening agents may aŠect the disintegration or dissolution of magnesium oxide. 3) In addition, the thickening agents may also aŠect the disintegration of quick-dissolving tablets such as oral-disintegrating tablets. 4,5) In this report, we examine the eŠect of immersion of a thickening agent on the inhibitory eŠect of frequently administered voglibose oral-disintegrating tablets on the incremental elevation of blood sugar levels, with the aim of improving post-prandial hyperglycemia in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…3) In addition, the thickening agents may also aŠect the disintegration of quick-dissolving tablets such as oral-disintegrating tablets. 4,5) In this report, we examine the eŠect of immersion of a thickening agent on the inhibitory eŠect of frequently administered voglibose oral-disintegrating tablets on the incremental elevation of blood sugar levels, with the aim of improving post-prandial hyperglycemia in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the current findings, although xanthan gum-based food thickeners are commonly used in medical institutions and nursing-care facilities, they should not be readily mixed with M tablet suspensions and administered to patients. In a previous study, 8) we showed that when Tsuru-Q was mixed in an M tablet suspension, the dissolution rate of MgO was greater than 80% 120 min after the start of the test. The difference with the present study was the length of time that the samples were allowed to stand for.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we allowed all samples to stand for 30 min, whereas previous studies did not specifically set a standing time. Moreover, because interviews conducted with those working in clinical practice revealed that up to 30 min is needed to mix food thickeners in an M tablet suspension before administration to patients, 8) we let the solutions used in the present study stand for 30 min. The results of the two studies, which had differing mixture standing times show that when Tsuru-Q is used, the effects on the dissolution rate of MgO is minimal, directly after mixing with the M tablet suspension, but the dissolution rate decreased when allowed to stand for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation